ANALYSIS OF FACTORS AFFECTING IN USING OF THE EMBROCATION PRODUCT OF CAP LANG BRANDS (A Case Study Society Umbulharjo village, Sleman, Yogyakarta) - Wahyudiyono, Hari; Darini, M.Si, Dra. Sri; Murdo,M.Si, Drs. Yuri (Management, 2010)
Research with the title of Analysis of Factors Affecting In Using of The Embrocation Product of Cap Lang Brands was conducted in November to December of 2008 with the respondent are Society of Umbulharjo Village, Sleman, Yogyakarta. This study aims to determine and analyze whether the price, quality, packaging and security stamp brand ointment lang influence public perception Umbulharjo village, Sleman, Yogyakarta. Data collection methods used were interviews and questionnaires. While the methods of data analysis used in this research is descriptive analysis method and quantitative measurement method which can be expressed with numbers. Based on the analysis of multiple linear regression equation with t test results can be seen that the rub oil prices affect the perception of the brand cap lang Umbulharjo Community Village, Sleman, Yogyakarta with t count for more than t table (2.566> 2.011). Quality brand ointment stamp lang affect perception Umbulharjo Village Society, Sleman, Yogyakarta. with t count more for than t table (3.510> 2.011). Packaging cap brand ointment lang affect perception Umbulharjo Village Society, Sleman, Yogyakarta with t count more for than t table (2.768> 2.011). Assurance rubbing oils affect the perception of the brand cap lang Umbulharjo Village Society, Sleman, Yogyakarta with t count more for than t table (3.098> 2.011). In calculating the F test results also can be seen that price, quality, packaging and security stamp brand ointment lang jointly affect public perception Umbulharjo village, Sleman, Yogyakarta, with a calculated F value is greater than F table (20.959> 13.90). Among the variables tested was the variable quality has the highest value so that the oil quality stamp pads lang most dominant brand in influencing public perceptions Umbulharjo village, Sleman, Yogyakarta. with a beta coefficient of 0.353 is greater than the price that has a value of 0117, the packaging that has a value of 0.181, and assurance that has a value of 0.116.Broadly speaking community perception Umbulharjo Village, Sleman, Yogyakarta on brand ointment stamp lang influenced by the quality, packaging, pricing and warranty with regression values of 0.685 or about 68.5% and 31.5% of them are influenced by other variables not included in this study. Keywords: embrocation, consumer perseption, quality, packaging, price.